The Value of the Naples Prognostic Score and the Systemic Immune-Inflammation Index in Predicting Ischemia on Myocardial Perfusion Scintigraphy - Hakan Süygün; Damla Yalçınkaya Öner; Ugur Nadir Karakulak (Diagnostics)
Objectives: Early identification of myocardial ischemia is critical for the management of patients with stable angina pectoris (SAP). The Naples Prognostic Score (NPS) and the Systemic Immune-Inflammation (SII) index are emerging biomarkers that may improve risk stratification prior to myocardial perfusion scintigraphy (MPS) Methods: We retrospectively analyzed 615 patients with SAP who underwent MPS to assess the predictive value of the NPS and SII index for myocardial ischemia. Clinical, laboratory, and imaging data were collected. The associations between the NPS, SII, and ischemia detected on MPS were evaluated through univariate and multivariate logistic regression analyses. Results: A higher NPS was strongly associated with the presence of myocardial ischemia (p < 0.001). Male sex, elevated SII, and increased C-reactive protein (CRP) and neutrophile-to-lymphocyte ratio (NLR) values were also significantly related to ischemia. In multivariate analysis, NPS (p < 0.001), SII (p = 0.023), CRP (0.005), and NLR (0.037) values remained independent predictors of ischemia. Albumin levels were significant in univariate analysis but lost independent significance after adjustment. The incorporation of the NPS and SII index provided additional value in identifying patients at high risk of ischemia. Conclusions: The NPS and the SII index are inexpensive, very simple, non-invasive, and valuable markers of myocardial ischemia in patients with SAP. Their integration into clinical practice may enhance risk stratification and optimize diagnostic pathways, minimizing unnecessary invasive procedures.